Thoracic Endovascular Aortic Repair (TEVAR): A Case Report - Hossain, GM Mokbul; Bashar, AHM; Hakim, Mohammad Enamul; Hossain, Md Fidah; Dey, Nirmal Kanti; Mamun, Abdullah Al; Sarker, Swadesh Ranjan; Arif, Ashfaq; Mandal, Naresh Chandra (Bangladesh Heart Journal, 2019)
Thoracic aortic aneurysm (TAA) is generally a disease of the elderly which remains mostly asymptomatic. It is often detected incidentally with imaging studies of the chest done for other reasons. We present a 55year-old smoker, normotensive and non-diabetic male patient who was diagnosed as a case of TAA and treated by endovascular means with thoracic endovascular aortic repair (TEVAR) technique. Due to small caliber femoral artery, thoracic endograft was deployed through a Dacron graft conduit of 10 mm diameter which was anastomosed to the common iliac artery. It was a hybrid procedure done in cardiac catheterization laboratory under general anesthesia. Completion angiogram revealed good technical success with no endoleak or neurological deficit. Patient improved symptomatically after TEVAR. Bangladesh Heart Journal 2019; 34(2) : 146-150